The Effect Of Competence And Motivation On Organizational Performance At The Development Of Dinas Bina Marga Dan Sumber Daya Air Kota Bekasi (Department Of Highways And Water Resources In Bekasi City) - Setyowati, Dwi; Tusoleha Rony, Zahara; Nurbaiti, Beti (UI Scholars Hub, 2022)
This study aims to analyze whether or not there is a relationship between competence and organizational performance, as well as motivation to organizational performance at the Department of Highways and Water Resources of the Former City. The population of this research is Civil Servants at the Department of Highways and Water Resources of Bekasi city, totaling 158 people, where all employees are the research sample. Variable measurements were performed using a Likert Scale. The analytical technique used in this research is SEM-LISREL version 8.8. The results showed that there was a significant relationship between competence and motivation on organizational performance.